(Bad) reputation in relational contracting. Issue 2 (25th May 2022) - Deb, Rahul; Mitchell, Matthew; Pai, Mallesh M.
Abstract : Motivated by markets for "expertise, " we study a bandit model where a principal chooses between a safe and risky arm. A strategic agent controls the risky arm and privately knows whether its type is high or low. Irrespective of type, the agent wants to maximize duration of experimentation with the risky arm. However, only the high type arm can generate value for the principal. Our main insight is that reputational incentives can be exceedingly strong unless both players coordinate on maximally inefficient strategies on path. We discuss implications for online content markets, term limits for politicians, and experts in organizations.